2022
DOI: 10.3390/biomedicines10123113
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Long COVID; Mitochondrial Health and Adaptation—Old Pathways, New Problems

Abstract: Many people infected with the SARS-CoV-2 suffer long-term symptoms, such as “brain fog”, fatigue and clotting problems. Explanations for “long COVID” include immune imbalance, incomplete viral clearance and potentially, mitochondrial dysfunction. As conditions with sub-optimal mitochondrial function are associated with initial severity of the disease, their prior health could be key in resistance to long COVID and recovery. The SARs virus redirects host metabolism towards replication; in response, the host can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 240 publications
0
28
0
2
Order By: Relevance
“…Therefore, improvement of mitochondrial dysfunction could be purposed as a therapeutic target of long COVID treatment. It has also been suggested that antioxidants may be able to stabilize mitochondrial function . In other words, supplementing phytochemicals that exhibit antioxidant capability or are able to support cellular antioxidant systems might achieve the aim of maintaining mitochondrial health.…”
Section: Mitochondria and Covid-19/long Covidmentioning
confidence: 99%
“…Therefore, improvement of mitochondrial dysfunction could be purposed as a therapeutic target of long COVID treatment. It has also been suggested that antioxidants may be able to stabilize mitochondrial function . In other words, supplementing phytochemicals that exhibit antioxidant capability or are able to support cellular antioxidant systems might achieve the aim of maintaining mitochondrial health.…”
Section: Mitochondria and Covid-19/long Covidmentioning
confidence: 99%
“…All this can be considered a collateral effect of cellular sequestration by the virus to redirect cellular metabolism towards viral replication. Although this condition usually reverses after viral clearance, its chronification may be associated with symptoms of mitochondrial-associated long COVID, which in turn may be a consequence of previous suboptimal mitochondrial function [45]. In this sense, the cellular mechanisms that eliminate damaged mitochondria lose their effectiveness and, consequently, they accumulate in the cells.…”
Section: Cytopathic Effects On Mitochondriamentioning
confidence: 99%
“…Other emerging studies suggest that SARS-CoV-2 induces chronic inflammation, increased ROS production and a dysbalanced metabolic state due to mitochondrial dysfunction, especially in patients with previous suboptimal mitochondrial function and low mitochondrial reserve due to factors like comorbidities or age [326]. In this context, the release of oxidized DNA fragments from damaged mitochondria activating the NLRP3 inflammasome, is thought to be a driving force of chronic inflammation [327].…”
Section: Possible Long-term Effects Of Sars-cov-2 Infectionmentioning
confidence: 99%